2021
DOI: 10.1186/s13027-021-00382-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between PEG3 DNA methylation and high-grade cervical intraepithelial neoplasia

Abstract: Background Epigenetic mechanisms are hypothesized to contribute substantially to the progression of cervical intraepithelial neoplasia (CIN) to cervical cancer, although empirical data are limited. Methods Women (n = 419) were enrolled at colposcopic evaluation at Duke Medical Center in Durham, North Carolina. Human papillomavirus (HPV) was genotyped by HPV linear array and CIN grade was ascertained by biopsy pathologic review. DNA methylation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, the hypomethylation observed in our current study seems to be independent of HPV infection, given the similar methylation levels between the HPV+ and HPV- samples considering either p16 INK4a and hrHPV markers. Similarly, H19DMR hypomethylation was not associated with HPV infection in invasive cervical cancer (ICC) [ 45 ] and cervical intraepithelial neoplasia (CIN) [ 46 ]. We previously showed that the 5mC Global DNA methylation mark is increased in penile SCC and is not influenced by HPV infection [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the hypomethylation observed in our current study seems to be independent of HPV infection, given the similar methylation levels between the HPV+ and HPV- samples considering either p16 INK4a and hrHPV markers. Similarly, H19DMR hypomethylation was not associated with HPV infection in invasive cervical cancer (ICC) [ 45 ] and cervical intraepithelial neoplasia (CIN) [ 46 ]. We previously showed that the 5mC Global DNA methylation mark is increased in penile SCC and is not influenced by HPV infection [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has validated that increased methylation at the promoters of several genes (CADM1, MAL, miR-124-2, FAM19A4, POU4F3, EPB41L3, PAX1, and SOX1) and HPV16 L1/L2 correlates to CIN lesion, with good performance in the triage of advanced CIN (20). While PEG3 methylation is associated with advanced CIN lesions (98), its efficacy for screening CIN/ICC needs to be further investigated. Because 3q gain is common in ICC, methylation of three genes (GHSR, SST, and ZIC1) is associated with 3q gain as well as the severity of CIN (99).…”
Section: Other Genesmentioning
confidence: 99%